SEG Technical Program Expanded Abstracts 2003 2003
DOI: 10.1190/1.1844071
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of time‐lapse seismic monitoring for heavy oil reservoir development — The rock‐physical basis

Abstract: We present a feasibility study for monitoring SAGD enhanced oil recovery with seismic methods in Western Canada. We determine the change in the elastic properties of the reservoir after steam injection based on well logs, a realistic but simplified steam chamber model, and the assumption that Gassmann's equation is applicable. Our calculations indicate that the seismic properties of the reservoir do not change substantially in this particular case without additional geotechnical effects, and therefore monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Production logging in this well confirmed the interpretation that after two years of steam injection, the full length of the horizontal well had been heated. Theune et al (2003) and Theune (2004) modeled the anticipated seismic responses due to steam injection into this reservoir that incorporated fluid substitution of steam and water for bitumen under expected in situ conditions. Because the Senlac reservoir is relatively thin (approximately 10 m), it was suggested that seismic monitoring of the reservoir would be difficult because traveltime attributes were not observable.…”
Section: Steam Flood Monitoringmentioning
confidence: 99%
“…Production logging in this well confirmed the interpretation that after two years of steam injection, the full length of the horizontal well had been heated. Theune et al (2003) and Theune (2004) modeled the anticipated seismic responses due to steam injection into this reservoir that incorporated fluid substitution of steam and water for bitumen under expected in situ conditions. Because the Senlac reservoir is relatively thin (approximately 10 m), it was suggested that seismic monitoring of the reservoir would be difficult because traveltime attributes were not observable.…”
Section: Steam Flood Monitoringmentioning
confidence: 99%